Problems of Limiting State Power From A Constitutional Perspective In Indonesia - Muhammad Farhan Nefaldy; Tomson Situmeang (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
This study aims to analyze constitutional challenges in limiting state power in Indonesia, particularly executive dominance, institutional oversight, and the effectiveness of constitutional control mechanisms, as well as to examine the obstacles and possible solutions. The novelty of this study lies in its integrated analysis of executive dominance, Constitutional Court controversies, and constitutionalism within a single analytical framework. This research employs a normative legal method with statutory and conceptual approaches, analyzed qualitatively. The results show that the limitation of state power has not been optimally implemented, as indicated by the dominance of executive power (executive heavy), weak effectiveness of oversight, and unclear boundaries of authority among state institutions. Based on Montesquieu’s theory of separation of powers, this condition reflects that the mechanism of checks and balances has not functioned ideally within Indonesia’s constitutional system. Furthermore, the obstacles in limiting state power include weak integrity and independence of state institutions, vague legal norms, low constitutional awareness, and ineffective oversight mechanisms. Based on Jimly Asshiddiqie’s theory of constitutionalism, this condition indicates that the function of the constitution as a limitation of power has not been optimally implemented. Therefore, it is necessary to strengthen institutions, harmonize legal norms, enhance constitutional awareness, and develop preventive oversight mechanisms to realize an effective limitation of state power in accordance with the principles of the rule of law.